Review of WFP Food Assistance Programming Practices in Southern Sudan - Maxwell, Daniel; Sim, Amanda; Mutonyi, Mercy (Tufts Archival Research Center, 2005)
The World Food Programme has been providing humanitarian food assistance to vulnerable communities and groups in Southern Sudan for over twenty years, but circumstances have changed following the signing of the Comprehensive Peace Agreement (CPA) in January 2005. The Feinstein International Center undertook this review of programs in Southern Sudan to help WFP Sudan make the needed changes to adapt to these new circumstances. The objective of this study is to improve programming in the 2007 EMOP and the subsequent PRRO. The Feinstein International Center views this as one step to building a long-term partnership with WFP Sudan.